Disagreement Between Heavy Equipment Tax Regulations and The Mandate of The Constitutional Court Decision on Road and Environmental Damage Variables - Mardiana, Mardiana; Purwanti, Riza; Pribadi, Denny Slamet (PT. Anagata Sembagi Education, 2025)
This study examines in depth the disharmony between the Heavy Equipment Tax provisions in Law No. 1 of 2022 concerning Financial Relations between the Central Government and Local Governments and the mandate of Constitutional Court Decision No. 15/PUU-XV/2017. The research focuses on the inconsistency in the formulation of the basis for imposition and characteristics of Heavy Equipment Tax, which has not internalized the variables of road damage and environmental impact as negative externalities from the use of heavy equipment. The main legal problem lies in the absence of the integration of road/environmental damage weight coefficients as previously known in the Motor Vehicle Tax (PKB) regime, so that the regulatory objectives that should reflect the regulatory function are not achieved. In addition, the lack of clarity in the legal approach is evident in the methodological choice of the legislators, who only adopted a budgetary approach without considering the conceptual approach of the polluter pays principle and the relevant Pigouvian tax theory to control the externalities of heavy equipment. This study is a normative (doctrinal) legal study using a statute approach to assess the conformity of the HKPD Law with the Constitutional Court's decision and a conceptual approach to examine the need to include road and environmental damage variables in the design of heavy equipment tax. The results show that heavy equipment tax regulations in the HKPD Law are still oriented solely towards budgetary functions, without adequate regulatory instruments to correct the negative externalities of heavy equipment use on public roads and in operational areas. The conclusion of the study confirms that the failure to fulfill the Constitutional Court's mandate has led to uncertainty in the concept of heavy equipment tax regulation and resulted in a lack of synchronization between the constitutional goal of environmental protection and the design of regional fiscal policy.